Enhancement factors in electrochemical surface oxidation enhanced Raman scattering. (1st June 2021) - Hernandez, Sheila; Perales-Rondon, Juan V.; Heras, Aranzazu; Colina, Alvaro
Highlights: EC-SOERS enhancement factors are assessed for the first time. EC-SOERS analytical enhancement factors higher of 10 5 were obtained. Substituent groups play a fundamental role in the enhancement of the Raman signal. Some kind of plasmonic structure is generated during the oxidation of silver. Abstract: Electrochemical Surface Oxidation Enhanced Raman Scattering (EC-SOERS) is a new phenomenon that provokes the enhancement of the Raman signal during the oxidation of a metal surface. Studies carried out so far indicate that carbonyl and carboxyl group are necessary to observe this phenomenon with a delocated charge being an important factor. In this work, the enhancement factors of EC-SOERS for different molecules, which present highly delocated charge and a carboxyl group, have been assessed. The systematic study of the enhancement factors helps to shed more light on the interaction of the molecules with the electrochemically generated SOERS substrates, yielding key information about the properties and specific features of this intriguing phenomenon. For the first time, a systematic information about the enhancement factors of this phenomenon is obtained. Analytical enhancement factors higher than 10 5 are obtained. Graphical abstract: Image, graphical abstract